2014
DOI: 10.1111/gwat.12186
|View full text |Cite
|
Sign up to set email alerts
|

Focused Groundwater Controlled Feedbacks into the Hyporheic Zone During Baseflow Recession

Abstract: Groundwater surface water interaction in the hyporheic zone remains an important challenge for water resources management and ecosystem restoration. In heterogeneous stratified glacial sediments, reach-scale environments contain an uneven distribution of focused groundwater flow occurring simultaneously with diffusely discharging groundwater. This results in a variation of stream-aquifer interactions, where focused flow systems are able to temporally dominate exchange processes. The research presented here inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…We found evidence of focused groundwater discharge both among and within transects when seepage was estimated based on Darcy's Law. Several other investigators have observed a high degree of spatial variation in groundwater discharge (Binley et al, ; Lowry, Walker, Hunt, & Anderson, ; Malzone & Lowry, ; Rosenberry, Briggs, Delin, & Hare, ) or hydraulic conductivity (Genereux et al, ) in streambeds. Based on the finding of other investigators and our previous work in Emmons Creek (Stelzer, Drover, et al, ), the determination of focused discharge in the study reach was not surprising.…”
Section: Discussionmentioning
confidence: 96%
“…We found evidence of focused groundwater discharge both among and within transects when seepage was estimated based on Darcy's Law. Several other investigators have observed a high degree of spatial variation in groundwater discharge (Binley et al, ; Lowry, Walker, Hunt, & Anderson, ; Malzone & Lowry, ; Rosenberry, Briggs, Delin, & Hare, ) or hydraulic conductivity (Genereux et al, ) in streambeds. Based on the finding of other investigators and our previous work in Emmons Creek (Stelzer, Drover, et al, ), the determination of focused discharge in the study reach was not surprising.…”
Section: Discussionmentioning
confidence: 96%
“…However, the most common method used to characterize hyporheic exchange—the analysis of solute tracer breakthrough curves—has failed to identify consistent controls on hyporheic exchange under time‐variable hydrologic conditions [e.g., Ward et al ., ; Payn et al ., ]. To‐date, time‐variable hyporheic exchange has been reported in response to variable base flow conditions [ Ward et al ., ; Payn et al ., ; Ward et al ., ], diel fluctuations in discharge [ Loheide and Lundquist , ; Sawyer and Cardenas , ; Sawyer et al ., ; Wondzell et al ., ], and storm event responses [ Ward et al ., ; Malzone and Lowry , ; Schmadel et al ., ]. Several studies that include high replication in space or through storm events report that observed variations in reach‐scale tracer transport and inferred hyporheic exchange could not be explained by discharge alone [ Wondzell , ; Ward et al ., ; Payn et al ., ; Ward et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…Elton Creek is a gaining stream; however, groundwater gradients are not high enough to contract the hyporheic zone completely. Heterogeneities in the sandy gravel deposit (clay lenses and gravel conduits) produce focused groundwater discharge in addition to diffuse groundwater discharge (Malzone and Lowry ). Pools and riffles comprise the majority of streambed topography with some steps and planar beds (Figure B).…”
Section: Introductionmentioning
confidence: 99%